PERAN GENERASI Z DALAM MENGAWAL DEMOKRASI DAN PEMILU 2029: ANALISIS PARTISIPASI MAHASISWA DALAM MENCEGAH POLARISASI SOSIAL DAN HOAKS POLITIK - Marsha Diva Damayanti; Meutia Hasanah Efendy; Ines Devita Anggraeni (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2026)
Digital transformation has significantly changed the political communication patterns of society, especially for Generation Z, who grew up in an internet- and social media-based environment. This generation is a strategic group in the democratic process because they have broad access to political information and the ability to build public opinion through digital platforms. Ahead of the 2029 General Election, the political participation of Generation Z, especially students, has increased, marked by active involvement in political discussions, digital campaigns, voter education, and digital literacy movements. However, the high intensity of social media use also poses challenges in the form of social polarization, hate speech, echo chambers, and the spread of political hoaxes that have the potential to disrupt democratic stability. This study aims to analyze the role of Generation Z in maintaining the quality of democracy and overseeing the implementation of the 2029 General Election by increasing critical and responsible political participation. The study used a qualitative approach with a literature study method of various scientific journals, academic articles, and official documents relevant to the themes of digital democracy, political participation, and digital literacy. The results show that students as part of Generation Z have an important role as agents of change, social controllers, disseminators of credible information, and pioneers of digital literacy in dealing with political hoaxes. Nevertheless, the low ability to verify information and the high level of exposure to disinformation remain major challenges that must be addressed through strengthening digital literacy education and media ethics. This research is expected to contribute to strengthening the quality of Indonesian democracy to be healthier, more participatory, and inclusive in the digital era.